Martha from the margins : the authority of Martha in early Christian tradition - Ernst, Allie M. (Vigiliae Christianae, Supplements, 2009)
In the popular imagination Martha has become synonymous with the harried housewife, fretting over excessive preparations. The Martha known to early Christians is far removed from this stereotype. Martha was better known for her role in the story of the raising of Lazarus and as apostle and witness of the resurrection. This book gathers and assesses the early traditions about Martha in text, liturgy and iconography. It shows that the significance of Martha has been seriously underestimated and recovers an important and widespread tradition of Martha as apostle and authority figure for early Christians. The analysis of Martha traditions with attention to issues of gender and authority render this book an important contribution to studies on women in early Christianity.